Preparation Of Cerium Dioxide Nps And Its Adoption In Biomedical Applications (Journal of the College of Basic Education, 2024)
A simple chemical approach was used to synthesize cerium dioxide (CeO2) NPss (NPs). UV-Visible , (FTIR), (XRD) and (SEM) were used to characterize the CeO2 NPs. It was found that band gap of the CeO2 NPs (Eg = 4.1 electron volt) was enlarged as compared to bulk ceria (Eg = 3.19 electron volt) based on UV-Vis analysis. SEM scans indicated spherical-shaped particles with a diameter of 47.68 nm, which were verified by FTIR data at 594 cm-1. Additionally, the generated CeO2NPs' antibacterial and antifungal efficacies were assessed, and the results showed that CeO2 NPs had both antibacterial and antifungal activity. Activities had varied values because the two groups' cell walls and membranes had distinct compositions.